Claretta : Mussolini's last lover - Bosworth, R. J. B., 1943- 07.12.1943- (Yale University Press, 2017)
"Few deaths are as gruesome and infamous as those of Benito Mussolini, Italy's fascist dictator, and Claretta (or Clara) Petacci, his much-younger lover. Shot dead by Italian partisans after attempting to flee the country in 1945, the couple's bodies were then hanged upside down in Milan's main square in ignominious public display. This provocative book is the first to mine Clara's extensive diaries, family correspondence, and other sources to discover how the last in Mussolini's long line of lovers became his intimate and how she came to her violent fate at his side. R.J.B. Bosworth explores the social climbing of Claretta's family, her naive and self-interested commitment to fascism, her diary's graphically detailed accounts of sexual life with Mussolini, and much more. Brimful of new and arresting information, the book sheds intimate light not only on an ordinary-extraordinary woman living at the heart of Italy's totalitarian fascist state but also on Mussolini himself"...